Pelatihan Keterampilan Dasar Komputer dan Teknologi Informasi Bagi Perangkat Desa se-Kecamatan Gangga - Sandi Justitia Putra; Zulhadi Zulhadi (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2021)
Basic Computer Skills and Information Technology Training for Village Apparatus in Gangga Subdistrict, North Lombok Regency. Community Service (PkM) is an effort by a service team to contribute science and technology to the community. Based on this, the team submitted a proposal for PkM activities in Gangga District, North Lombok Regency. The purpose of this PkM is to provide basic computer skills and information technology training to village officials throughout the Gangga District. This training is expected to provide provisions for village officials about the benefits of computers and information technology (internet), especially in terms of developing knowledge and solving problems related to administrative work of village officials. The output target of this activity is that the training participants are equipped in terms of operating computers, can use computers and the internet to solve various problems encountered, and can improve the quality of service to stakeholders, especially in terms of effectiveness and efficiency in various fields.